ANALISIS PERAMALAN NILAI EKONOMI INDUSTRI AMPLANG DI KOTA SAMARINDA - Safitra Dea Miranda; Bambang Indratno; Heru Susilo (2339-1324, 2020)
The purpose of this research is to find out the best forecasting method to see production and to know the economic value produced by the amplang industry in the future. This research was conducted in Samarinda City. Samples were 19 envelopes in Samarinda which were obtained using the Slovin formula and the sampling method used was the Purposive Sampling method. The results show that: the exponential growth model is the best calculation model based on the results of the test model and the smallest standard error value is 0.012. Both methods used show the results of an increase in the amount of production in the future that is equal to 521.09 kg for the linear trend method while 495.46 for the exponential growth method